Addressing Barriers to Health Care Access of Congenital Heart Disease Patients in Guyana - Sarah Ames MD; Emma Pillsworth MPH, MD; Arnelle Sparman-Shelto MD; Debra Lynne Isaac MD (SAGE Publishing, 2021)
In order to mitigate the late presentation and resulting poor outcomes of children with advanced cardiac disease, the Ministry of Public Health (MOPH) in Guyana has expressed interest in identifying ways to improve access to health care for these children. The goal of this study was to identify barriers faced by CHD patients and their families in accessing pediatric cardiology services in Guyana, and to identify limitations to the diagnosis and referral of CHD patients by health care professionals. Two surveys were used to gain insight into the experiences of practicing health care professionals and the parent(s) or guardian(s) of children with CHD. Patients were identified based on convenience sampling at cardiology clinics and outreach clinics in both urban and rural Guyana. Physicians were identified using convenience sampling at health posts in rural Guyana. Fifty-two (n = 52) families were identified and interviewed throughout the regions visited. The majority of families identified distance, the need to travel, and their inability, financially and practically, to attend clinic as the main barrier to accessing specialized care. Twelve (n = 12) health care providers were interviewed. They identified limited knowledge surrounding the diagnosis and management of CHD, and perceived impracticality of referring patients to specialized services, despite being aware of the referral process. This study identifies the need for improved outreach and support for health care providers and families, especially those living in rural communities. It identifies some of the challenges faced in managing patients with CHD in Guyana, while establishing specific areas for quality improvement.